TINJAUN YURIDIS PERJANJIAN JUAL BELI TANAH SECARA ANGSURAN DI KOTA SAMARINDA - Risky Rahmadii Salam (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTLand ownership is very important for the country, nation and people of Indonesia as a society that is building towards the development of industry. Land that is a basic need for human beings will be faced with various things such as land limitations both in quantity and quality compared with the needs that must be met.The abolition of this agreement is due to the inability of the buyer in this case the buyer to settle the purchase price on a plot of land previously agreed with the seller. The inability of repayment is then used as the basis or reason for the buyer to cancel the sale and purchase of a piece of land.While the legal protection is repressive that is legal protection given if there has been a dispute that the injured party in the sale and purchase agreement is actively taking legal action by filing a civil lawsuit to the local District Court to cancel the sale and purchase agreement on the land, The fairest verdict.Keywords: Purchase of Land, Repurchase Rights